Menakar Relevansi Metode Pembelajaran Konvensional Pada Pendidikan Islam di Era Digital - Saadah, Neng Siti Nur; Anggraeni, Reni; fitriani, Dwi awaliyah (Penerbit Widina, Widina Media Utama, 2025)
This study aims to examine the role of technological innovation in the transformation of Islamic education in the digital age. This study uses a literature review approach, relying on secondary data collected from written sources such as books, academic journals, articles, and other relevant documents. The findings of this study indicate that technological innovation plays a crucial role in this transformation by facilitating the wider and more effective dissemination of Islamic knowledge, improving the quality and accessibility of learning, and overcoming various challenges. However, issues such as the digital divide and human resource readiness must be addressed to ensure the successful adoption of technology in Islamic education. The transformation of Islamic education in the digital age is a complex and multifaceted process, involving changes in teaching methods, curriculum, learning materials, as well as pedagogical and ethical frameworks. Although this transformation presents challenges, it also offers significant opportunities to improve the quality of education and the dissemination of Islamic teachings.ABSTRAKPenelitian ini bertujuan untuk mengkaji peran inovasi teknologi dalam transformasi pendidikan Islam di era digital. Penelitian ini menggunakan pendekatan tinjauan literatur, dengan mengandalkan data sekunder yang dikumpulkan dari sumber tertulis seperti buku, jurnal akademik, artikel, dan dokumen relevan lainnya. Temuan penelitian menunjukkan bahwa inovasi teknologi memainkan peran krusial dalam transformasi ini dengan memfasilitasi penyebaran pengetahuan Islam yang lebih luas dan efektif, meningkatkan kualitas dan aksesibilitas pembelajaran, serta mengatasi berbagai tantangan. Namun, masalah seperti kesenjangan digital dan kesiapan sumber daya manusia harus diatasi untuk memastikan adopsi teknologi yang sukses dalam pendidikan Islam. Transformasi pendidikan Islam di era digital merupakan proses yang kompleks dan multifaset, melibatkan perubahan dalam metode pengajaran, kurikulum, bahan pembelajaran, serta kerangka pedagogis dan etis. Meskipun transformasi ini menghadirkan tantangan, ia juga menawarkan peluang signifikan untuk meningkatkan kualitas pendidikan dan penyebaran ajaran Islam.